Comparison of the SYNTAX score 2020 based on Coronary Artery Computed Tomography (CCTA) with Invasive Coronary Angiography (ICA). (3rd October 2022) - Masuda, S; Kageyama, S; Kotoku, N; Ninomiya, K; Schneider, U; Doenst, T; Tanaka, K; Mey, J D; Lameir, M; Mushtaq, S; Bartorelli, A; Pompilio, G; et al.
Abstract: Introduction: The SYNTAX III REVOLUTION trial demonstrated that clinical decision-making between coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI) based on coronary artery computed tomography (CCTA) and predicting four years mortality according to the SYNTAX score II had a high agreement with the treatment decision derived from invasive coronary angiography (ICA). The agreement of the novel SYNTAX score 2020 (SS-2020) based on CCTA and ICA has not yet been evaluated in a prospective fashion. Methods: This study included 54 consecutive patients in the ongoing FASTTRACK CABG trial that investigates decision making, planning and procedural CABG guidance based solely on CCTA and FFRct. All the patients underwent CCTA and ICA, and SS-2020 was calculated based on the results of anatomical SYNTAX score derived from either CCTA or ICA, and the respective scores were compared by using paired t-test. Results: The mean age was 67.3±9.7, and 48 were men (88.9%). Anatomical SYNTAX score derived from CCTA was assessed in the 54 cases (analysability 100%). Anatomical SYNTAX scores based on CCTA and ICA were 34.3±9.3, and 35.5±11.3, respectively (P=0.480). As shown in the table predicted 5 years major adverse cardiac and cerebrovascular events (MACCE) following either PCI or CABG, as well as predicted 10 years mortality following CABG differed significantly. However the absolute risk differences (ARD) in 5 years MACCE and 10 years mortality following either PCI or CABG, were comparable. Conclusions: High agreements were confirmed in the calculations of anatomical SYNTAX scores with CCTA and ICA. Despite significant differences in predicted MACCE rates at 5 years and mortalities at 10 years, the ARD in MACCE rates and mortality were comparable. In terms of treatment decision-making, SS-2020 calculations based on CCTA is a non-invasive predictive tool comparable to the one based on ICA. Funding Acknowledgement: Type of funding sources: None.